Intercultural Communication Skills for Students of Sabilul Rahmah International Islamic Boarding School Pacet, Mojokerto - Pariyanto Pariyanto; Luluk Ulfa Hasanah; Sharmini Abdullah; Rozilawati Mahadi (Universitas Muhammadiyah Malang, 2025)
It is important to recognize that globalization has had a significant impact on the world of work. In this context, many companies recognize that cross-cultural communication skills are key to facilitating effective interactions between workers who come from heterogeneous cultural backgrounds. In addition, the phenomenon of an increasing number of individuals migrating from one country to another further strengthens the urgency of developing cross-cultural communication skills in the educational realm. The topic raised in this community service activity is in accordance with the needs of Sabilul Rahmah International Islamic Boarding School (Sabira-IIBS). Located in Sumberam, Sajen, Pacet, Mojokerto, East Java, Sabira IIBS is a pesantren education institution and Madrasah Aliyah (MA) level school with a learning system that combines traditional pesantren Islamic values with modern learning. The curriculum used is based on the national curriculum & international curriculum (Al Azhar University for diniyah & Cambridge for Math, Science & English). The school aims to prepare its graduates to become agents of change in accordance with the purpose of the graduation designation. Most santri are encouraged to continue their studies to favorite universities both domestically and abroad. This community service activity was carried out through collaboration between the Faculty of Cultural Sciences, Universitas 17 Agustus 1945 Surabaya and UniMap Malaysia Perlis. Based on the activities that have been carried out, it can be concluded that after the activity takes place there is an increase in the knowledge and understanding of the participants related to cross-cultural communication from an average understanding of 1.1 on a scale of 4 to 3.7 on a scale of 4. This indicates that the joint community service activities carried out by the academics of FIB Untag Surabaya in collaboration with the academics of Universiti Malaysia Perlis completed successfully and can achieve the goals or targets of this activity. As a result, this activity had a positive impact on increasing the knowledge and understanding of students of partners’ institution.